APPLICATION OF SHARIA PRINCIPLES IN THE FINANCIAL MANAGEMENT OF MSMEs IN INDONESIA AT POLMAN, SULBAR - Fauziah, Fauziah; Kara, Muslimin; Wahab, Abdul; Masse, Rahman Ambo; Sappeami, Sappeami (International Journal of Multidisciplinary Research and Literature, 2024)
This investigation aims to investigate the integration of sharia principles into the financial management of micro, small, and medium-sized enterprises (MSMEs) in Polman, West Sulawesi Island. In-depth interviews with MSME actors and regional Sharia financing institutions comprise the qualitative methodology employed in this investigation. This study found that applying sharia principles, such as the use of mudharabah and musyarakah-based financing, positively impacts business sustainability and development. Sharia principles help MSME actors manage resources fairly and transparently and avoid detrimental usury practices. However, the primary challenge is MSME actors' need to understand sharia principles and limited access to appropriate sharia financing institutions. These limitations prevent optimal implementation and reduce the potential benefits. Therefore, this study suggests the importance of increasing understanding through training and socialization regarding sharia principles, strengthening institutions, and accessing sharia financing institutions. Enhanced accessibility and comprehension of Sharia financing are anticipated to foster the growth of more sustainable MSMEs and promote an inclusive local economy